Creative Tourism as a strategy for institutional tourism bodies in Destination Development - Dias, Á.; Gato, M.; Maria Rosario González-Rodríguez (62nd International Scientific Conference on Economic and Social Development, 2021)
This paper analyses how fundamental the role of tourism organizations is when resorting to implementing dynamic activities and experiences in creative tourism, as alternatives to the current tendencies of mass tourism, in order to stimulate and develop tourism destinations by providing tourists with an active role when in contact with experiences that are typically found in these regions. In addition to the need of aiming to attract new visitors, institutional tourism bodies should ambition to increase re-visitation by enhancing engagement with the locals and interaction with stakeholders present in the tourism destination relying on co-creation and authentic participation. Therefore, our proposed conceptual model intends to demonstrate organizational learning and management of tourism destinations as key factors in a strong creative tourism environment that can generate value in these regions in a sustainable form. The findings from both the qualitative and quantitative studies in a range of institutional creative tourism bodies concluded that aligning organizational performance and market performance within the creative tourism context can contribute to the effective management of destinations.